Correlation Between Gene Expression of Interferon Regulatory Factor-5 and Disease Activity Index in Systemic Lupus Erythematosus Iraqi Patients - Dahham, Zainab M.; Haddad, Namir I. A. (Iraqi Journal of Science, 2023)
Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease characterized by elevated levels of circulating anti-nuclear autoantibodies and interferon-alpha (INFs-α). Interferon regulatory factor-5 (IRF5) plays an important role in the induction of type I interferon and pro-inflammatory cytokines, and participates in the SLE pathogenesis. This study aimed to investigate the role of IRF5 gene expression levels in a sample of SLE Iraqi patients and its correlation with disease activity, and to identify its diagnostic ability as a biomarker reflecting disease activity. Blood samples were taken from 45 participants diagnosed with SLE cases classified according to the American College of Rheumatology (ACR) criteria. They were scored via the SLE disease activity index 2000 (SLEDAI-2K) to assess the disease activity and according to it, they were subdivided into “SLE (I) group” (SLEDAI-2k ≤5), and “SLE (II) group” (SLEDAI-2k >5), as well as age and gender matched healthy control group. RNA was isolated from whole blood samples and gene expression levels of IRF5 were determined using real-time polymerase chain reaction (PCR). Our results revealed that the expression levels of the IRF5 gene were significantly increased in SLE (I) and SLE (II) patient groups compared with the control group (p<0.05, and p<0.01) respectively, as well as higher in SLE (II) group than the SLE (I) group (p<0.01). Moreover, the expression levels of IRF5 were found to be related positively and significantly to the disease activity index in both SLE patient groups. The analysis of receiver operator curves (ROC) for gene expression levels of IRF5 in SLE (II) group showed a perfect accuracy to distinguish between SLE patients and healthy individuals (AUC=0.989, sensitivity= 95.5%, and specificity= 88.0%). However, in SLE (I) group showed a good accuracy to discriminate between SLE patients and healthy individuals. (AUC=0.769, sensitivity= 69.6%, and specificity= 80.0%). The correlation between gene expression levels of IRF5 with other parameters revealed that a significant positive correlation was found with uric acid and ALP in SLE (I) group, while in SLE (II) group with urea, creatinine, and uric acid. Our conclusion suggests that the up-regulation of IRF5 gene expression levels correlates positively with disease activity in SLE patients reflecting the possibility of using it as an immunological biomarker for diagnosis, and monitoring the disease flare.